Problemy szacowania stopy dyskontowej z punktu widzenia mikro- i makroekonomicznej oceny efektywności inwestycji - Michalak, Aneta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article discusses problems of micro- and macroeconomic rating of investment effectiveness. It focuses on the net present value method. This method can be used for the microeconomic rating of effectiveness (the investor-led ratings), as well as for the macroeconomic rating (society-led retings). One of the parameters is discount. In the present paper, the investment discount is expressed by capital cost in the microeconomic rating, and by the social discount rate in the macroeconomic rating of investment effectiveness. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 270-283